Contrast Enhancement Using Curd and Contrast Agent Mixtures for Ex Vivo Vessel Imaging in Computed Tomography - Obert, M.; Kohl, L. M.; Graf, N.; Krombach, G. A.; Verhoff, M. A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
We describe a cheap and efficient method for filling the vascular space of ex vivo tissue samples with a radiopaque material that can be used in computed tomography imaging. The filling material consists of curd, water, and a radiological contrast agent. Viscosity ranges and the degree of attenuation of X-rays of the filling material can be easily adjusted to the requirements of a specific application. The method is non-destructive and without negative effects on subsequent histological examinations.